P018 Multi-disciplinary team management of haemophagocytic lymphohistiocytosis: improving patient outcomes in a central London teaching hospital. (26th April 2021) - Ludwig, Dalia R; Manson, Jessica; Jones, Alexis; Mackenzie, Strachan; Mccann, Naina
Abstract: Background/Aims   Haemophagocytic lymphohistiocytosis (HLH) is a syndrome characterised by the presence of severe uncontrolled systemic inflammation due the overproduction of inflammatory cytokines and macrophage activation. The majority of adult patients have secondary HLH, triggered by either infection, haematological malignancy or rheumatic disease. Early recognition and initiation of definitive treatment is of vital importance as HLH leads to multi-organ failure and death if left untreated, with mortality of up to 80% in some cohorts. Methods   Under-recognition of the disease and vast differences in the management of patients with HLH between specialities have been common problems. To address this, a Rheumatology-led HLH multi-disciplinary team (MDT) meeting was established at University College London Hospital (UCLH) in 2018. The MDT includes physicians from Rheumatology, Infectious Disease, Haematology, Intensive Care, Nephrology and Neurology and feeds into the national HLH group HASC - HLH Across Specialty Collaboration. The MDT is now held bimonthly, discussing between 2 and 4 cases each meeting. The MDT functions as a decision-making tool, while providing consensus on patient management, including collaboration on how to access urgent HLH-directed treatments such as Anakinra for secondary care centres without access. It also serves as a unique learning opportunity for trainees from different disciplines. Results   Since the introduction of the MDT the number of patients diagnosed with HLH at ULCH has increased from an average of 6 per year in 2014-2016 to 12 per year in 2018-2020. In the last two years we have seen improved survival from years 2017/18 to 2019/20 (Table 1 ); survival was approximately 30% in 2017 and 75% in 2019. Conclusion   We believe that the HLH MDT has directly contributed to these improvements by encouraging earlier recognition and subspeciality collaboration. We encourage other sites to adopt a multi-disciplinary approach to managing patients with HLH to promote awareness of the condition and improve patient outcomes. Disclosure   D.R. Ludwig: None. J. Manson: None. A. Jones: None. S. Mackenzie: None. N. Mccann: None.